Analisis Manajemen Antrean dan Efektivitas Pelayanan pada Bank Bapas 69 Kantor Kas Rejosari - Shefta Eka Praswati; Siti Arifah (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2026)
This study aims to examine how to manage queues and service quality at Bank Bapas 69 Rejosari Cash Office (KK), especially given the limited number of staff and the absence of a formal queuing system. Using a qualitative descriptive approach with a descriptive case study method, data was collected through participatory observation and interviews during the internship period from January - March 2026 internship period. This study  shows that the queue system is not yet functioning properly, as evidenced by the large number of customers crowding around the service desk. This is mainly due to the difficulty elderly customers have in taking care of administrative matters at the Teller desk, as well as the excessively long credit consultation time at the Customer Service desk. It can be concluded that the effectiveness of service at PD BPR Bank Bapas 69 Magelang (Perseroda) Rejosari Cash Office is still hampered by suboptimal queue management. This tangible contribution is expected to shape a more orderly, clear, and time-efficient service process for Bank Bapas 69 KK Rejosari without having to incur significant costs for technology.